Low-carbon high-stability modified asphalt and preparation method thereof

By using pretreated waste rubber bands to prepare low-carbon high-stable asphalt modifiers, the problems of SBS-modified asphalt aging and low recycling rate of waste rubber are solved, and the high-temperature stability and low-temperature crack resistance of asphalt are improved, and the service life of asphalt pavement is extended.

CN119552519APending Publication Date: 2025-03-04JSTI GRP CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411725521.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing SBS modified asphalt aging under conditions such as thermal oxidation and ultraviolet rays, resulting in a decline in physical and chemical properties, making it difficult to achieve the 15-year life required by the design, and the recycling rate of used rubber is low.

Method used

Use waste rubber bands as the main raw material, and prepare low-carbon high-stable asphalt modifiers through pretreatment and refining, and add them to matrix asphalt to improve its high-temperature stability, creep resistance and low-temperature crack resistance.

Benefits of technology

It significantly improves the high temperature stability and creep resistance of asphalt, extends the service life of asphalt pavement, and at the same time realizes the harmless and resource utilization of waste rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552519A_ABST
    Figure CN119552519A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of asphalt modification, in particular to low-carbon high-stability modified asphalt and a preparation method thereof.The low-carbon high-stability modified asphalt comprises matrix asphalt, a low-carbon high-stability asphalt modifier, a stabilizer and an accelerant, the doping amount of the low-carbon high-stability asphalt modifier is 2-10 wt% of the matrix asphalt, the doping amount of the stabilizer is 0.2-0.3 wt% of the matrix asphalt, and the doping amount of the accelerant is 0.75-1.75 times of the doping amount of the stabilizer. According to the prepared modified asphalt, the needle penetration is remarkably reduced, the softening point is improved, and the rotary viscosity at 135 DEG C in the aspect of constructability is excellent. The prepared modifier can effectively improve the high-temperature stability and creep resistance of asphalt, so that a green, high-performance and sustainable asphalt binder is produced. In addition, harmless and resource utilization of the waste rubber bands is achieved. The cost of the modified asphalt is reduced, and the dual purposes of environmental protection and economic benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of asphalt modification, and in particular to a low-carbon and highly stable modified asphalt and a preparation method thereof. Background Art

[0002] With the advancement of technology, asphalt pavement has gradually become popular, especially in modern engineering, SBS (styrene-butadiene-styrene) modified asphalt has become the most common binder. SBS is a petroleum-based material that is non-renewable and difficult to recycle, and is not sustainable. At the same time, the double bonds (C=C) present in the SBS modifier are easily aged under conditions such as thermal oxidation and ultraviolet rays, resulting in a decrease in physical and chemical properties. However, the increasing traffic load and the aging problem of SBS make it difficult for asphalt pavements to reach the 15-year lifespan required by the design. More than 70% of pavements require major or medium repairs within 10 years, resulting in a huge consumption of non-renewable resources. Therefore, the development of green road building materials is of great significance to achieving the sustainable development of the transportation industry.

[0003] With the rapid development of the automotive, medical and daily necessities industries, the demand for multifunctional rubber products has surged, and a large amount of waste rubber has also been generated. Due to the high durability, elasticity and chemical stability of these waste rubbers, traditional incineration and landfill treatment methods will pollute the environment and waste precious resources. In the field of waste rubber reuse, a relatively complete treatment system has been established, including technologies such as thermal cracking and recycled rubber production. However, these methods either have high energy consumption or have high requirements for raw materials, and have limitations. The high consumption of road building materials provides an ideal treatment method for waste rubber that is difficult to use efficiently. Since 2000, rubber-modified asphalt has been gradually promoted in my country and is currently widely used in high-grade pavements such as highways, urban roads and airport runways. Waste tire rubber is usually added to asphalt as the main raw material to improve the high temperature stability and rutting resistance of asphalt. However, since tire rubber has been vulcanized, its molecular structure is difficult to shear and disperse in the preparation of modified asphalt, resulting in strong thermodynamic incompatibility, easy stratification, and poor low-temperature crack resistance than SBS modified asphalt. These technical bottlenecks limit the further application of rubber modified asphalt.

[0004] Chinese patent document CN117624923A discloses a modified asphalt prepared from discarded polymer gloves and a preparation method thereof. The document points out that the modified asphalt prepared from polymer gloves made of pure natural rubber (latex) has improved the low-temperature performance of petroleum asphalt, but has no increase in high-temperature stability and other basic properties, and only maintains the performance range of unmodified petroleum asphalt.

[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a low-carbon and high-stability modified asphalt, which is prepared by using waste rubber bands (containing 60-90% latex) as raw materials to prepare a low-carbon and high-stability asphalt modifier for asphalt modification, which can effectively improve the high-temperature stability, creep resistance and low-temperature crack resistance of ordinary petroleum asphalt. At the same time, it solves the problem of single type of waste rubber used in the road building materials industry, increases the recycling market of waste rubber bands and other waste products, and improves the recycling rate of waste rubber.

[0007] Waste rubber bands have higher elasticity and ductility because they contain a high proportion of latex (natural rubber content is as high as 60% to 90%). Compared with the natural rubber content of only 20% to 40% in waste tire rubber, and a higher degree of vulcanization, waste rubber bands perform better in low-temperature crack resistance. Its lower degree of vulcanization leads to a lower cross-linking density, which is easier to shear and disperse during the asphalt modification process, and can form a more stable structure with the matrix asphalt. Therefore, the present invention intends to use waste rubber bands as the main raw material to prepare modifiers, so as to increase the recycling market for waste rubber bands, thereby realizing the harmless and resourceful utilization of rubber. This can not only effectively solve the environmental pollution problem caused by waste rubber, but also provide a new way for the development of sustainable transportation infrastructure.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A low-carbon and high-stability modified asphalt comprises a base asphalt, a low-carbon and high-stability asphalt modifier, a stabilizer and a promoter, wherein the dosage of the low-carbon and high-stability asphalt modifier is 2-10wt% of the base asphalt, the dosage of the stabilizer is 0.2-0.3wt% of the base asphalt, and the dosage of the promoter is 0.2-0.5wt%, which is 0.75-1.75 times that of the stabilizer.

[0010] Furthermore, the low-carbon and high-stability asphalt modifier is obtained by pre-treating waste rubber bands that have been stored for 3 to 6 months in a natural outdoor waste accumulation state and exposed to external environmental conditions such as heat, oxygen, and ultraviolet rays, and its latex content is about 60 to 70%.

[0011] The raw material of the low-carbon high-stable asphalt modifier of the present invention is waste rubber bands. The rubber bands are made of natural rubber (latex) as the main raw material, combined with synthetic rubber and fillers, anti-aging agents and cross-linking agents and other additives through a mixing method. The flexibility and elasticity are much higher than simple rubber particles. During the waste process, it is aged under environmental conditions such as thermal oxygen and ultraviolet. During the heat and thermal oxygen aging process, the density of EAC (elastic active chain) increases, so that the elastic recovery of the natural rubber after waste is improved, and the rigidity decreases, thereby improving the problem of natural rubber becoming brittle at low temperatures. On this basis, the unsaturated carbon bonds contained in natural rubber undergo a slow oxidation reaction with oxygen in the air during use and storage, thereby increasing the polarity, which can improve its compatibility with polar matrix asphalt.

[0012] If the natural rubber in the waste rubber bands has not been properly naturally oxidized and stabilized (such as too short storage time or poor condition), its polysulfide bond content is high and EAC (active elastic chain) is low, the efficiency of the cross-linking reaction with sulfur will be reduced, and the synergistic effect will not be significant. Rubber bands that have been stored for too long may have been over-aged or degraded, and the integrity and vulcanization potential of the molecular chain are insufficient, and the synergistic effect with sulfur cannot be fully exerted. Waste rubber bands that have been stored for a reasonable time (such as 3 to 6 months) have moderate polarity and complete molecular chains, which can participate in sulfur cross-linking to the maximum extent and exert the best synergistic modification effect.

[0013] Furthermore, the stabilizer is sulfur with a purity of 98%. Sulfur can form sulfur bonds such as monosulfide, disulfide and polysulfide between natural rubber at above 150°C, promoting the formation of a three-dimensional cross-linked network structure. This network can significantly enhance the strength and elasticity of natural rubber. The use of sulfur as a stabilizer in the present invention can further optimize this cross-linked network structure and further improve the high-temperature rutting resistance of asphalt. At the same time, the sulfur vulcanization reaction can inhibit the decomposition or volatilization of natural rubber molecules at high temperatures, maintain the effective content of natural rubber, and improve the compatibility of natural rubber and asphalt.

[0014] Further, the accelerator is N-cyclohexyl-2-benzothiazole sulfonamide (CBS), with a purity of ≥95%. This application uses CBS as an accelerator to accelerate the cross-linking reaction between sulfur and rubber molecules in waste rubber bands. CBS reduces the vulcanization temperature and accelerates the reaction rate by producing active sulfides and free radicals during the rubber vulcanization process, thereby improving production efficiency. In addition, the delay of CBS is good, so that the vulcanization reaction has a longer processing time window in the early stage, reducing the risk of premature vulcanization during mixing and molding. In addition, CBS can improve the utilization rate of sulfur, reduce sulfur residues, and ensure the modification effect and environmental friendliness of asphalt.

[0015] Furthermore, the treatment method of waste rubber bands is: place the waste rubber bands in a pulsator cleaning machine to clean and remove surface stains and dry them, the dried waste rubber bands are crushed once by a crusher to obtain larger particles, and then grind and screen them using a rubber mill (grinding shaft type) to obtain smaller particles, and repeat grinding and screening to obtain a low-carbon, high-stability asphalt modifier with a particle size of ≤40 mesh.

[0016] Using pure natural rubber (a natural product of rubber tree) as a modifier, the effect of high temperature stability modification is not obvious due to the influence of its molecular chain polymerization degree, and synthetic rubber (such as tire particles) is difficult to obtain effective shear dispersion in the modified asphalt preparation process, which affects the modification uniformity. The waste rubber band used in the present invention has experienced appropriate aging during natural storage, improved surface polarity, and enhanced compatibility with polar asphalt matrix. This characteristic makes up for the shortcomings of pure natural rubber or synthetic rubber in miscibility. Waste rubber bands are prepared as microparticles with a particle size of ≤40 mesh during cleaning, drying, shearing and screening, and their own molecular weight is smaller than synthetic rubber, and can be more evenly dispersed in the asphalt matrix. In addition, the internal molecular chain of the waste rubber bands of appropriate aging remains stable at high temperatures, avoiding decomposition and odor problems.

[0017] Furthermore, the cleaning time is 2 to 3 hours. Preferably, a multi-stage cleaning step can be adopted, firstly cleaning with warm water (50°C to 60°C) to remove easily soluble dirt on the surface, and then using ultrasonic assisted cleaning to improve the stripping efficiency of insoluble dirt on the rubber band surface.

[0018] Furthermore, the drying condition is at 75° C. to 90° C. for 2 h to 4 h.

[0019] The second object of the present invention is to provide a method for preparing low-carbon and high-stability modified asphalt, which has the same technical effect.

[0020] In order to achieve the above object, the technical solution adopted by the present invention is:

[0021] A method for preparing low-carbon and high-stability modified asphalt comprises the following steps:

[0022] S1. Prepare a low-carbon and high-stability asphalt modifier for standby use;

[0023] S2, heat the base asphalt at 130-140°C for 30-35 minutes to melt it, then add 2-10wt% of the low-carbon high-stability asphalt modifier prepared by S1, control the temperature at 160-165°C, and stir it for 10-15 minutes;

[0024] In the method of the present invention, the low-carbon and high-stability asphalt modifier is initially dispersed in the matrix asphalt through preliminary stirring, and the preliminary stirring adopts low-speed stirring, such as manual stirring. The preliminary stirring can avoid the separation and stratification of the components of the modifier and the matrix asphalt in the next high-speed shearing process due to the different densities of the modifier and the matrix asphalt, which weakens the shearing effect. Further high-speed shearing can further grind the low-carbon and high-stability asphalt modifier, and the high-speed shearing process is generally carried out using a high-speed shearing instrument. Further high-speed stirring can make the asphalt modifier after high-speed shearing grinding be further dispersed in the matrix asphalt, and the high-speed stirring and dispersion process is generally carried out in a high-speed agitator.

[0025] S3. After preliminary stirring, the mixed material is subjected to high-speed shearing for 40 to 50 minutes, the high-speed shearing rate is 4500 to 5000 r / min, and the temperature is controlled at 170 to 175°C;

[0026] S4, add 0.2-0.3wt% of stabilizer, control the temperature at 170-180°C, stir for 5-10min to mix evenly, and then perform high-speed dispersion stirring at a rate of 400-500rad / min; the time of high-speed dispersion stirring is controlled at 15-25min, and the temperature is controlled at 170-180°C.

[0027] S5. Add accelerator at a dosage of 0.75 to 1.75 times that of stabilizer, continue high-speed dispersion stirring at a rate of 400 to 500 rad / min, control the time at 20 to 25 minutes, and control the temperature at 175±3°C to obtain low-carbon and high-temperature modified asphalt.

[0028] The beneficial effects of the present invention are:

[0029] 1. The present invention proposes a new method for preparing a low-carbon and high-stability asphalt modifier using waste rubber bands. After applying it to the modification of ordinary petroleum asphalt, the needle penetration is significantly reduced, the softening point is increased, and the rotational viscosity at 135°C is relatively excellent in terms of workability. This shows that the prepared low-carbon asphalt modifier can effectively improve the high-temperature stability and creep resistance of asphalt, thereby producing a greener, high-performance and sustainable asphalt binder. In addition, the asphalt modifier prepared using waste rubber bands can not only alleviate the "white pollution" environmental problem caused by the incineration or accumulation of waste rubber bands, but also realize the harmless and resource utilization of waste rubber bands. Through this method, the cost of modified asphalt can be reduced, achieving the dual goals of environmental protection and economic benefits.

[0030] 2. The present invention uses waste rubber bands as raw materials to prepare a low-carbon, high-stability asphalt modifier, the main components of which include an elastomer composed of 60-90% latex and a small amount of filler. The molecular chain of the rubber band is highly elastic. After being added to the matrix asphalt, it can produce a significant mechanical reinforcement effect on the matrix asphalt through its long chain structure. Under high-temperature shear conditions, with the introduction of a vulcanizing agent, the rubber molecular chain undergoes a cross-linking reaction to form a stable network structure, thereby improving the structural strength of the asphalt and enhancing its high-temperature flow resistance and creep resistance. In addition, this network structure can absorb light components in the matrix asphalt, increase the relative content of colloid and asphaltene, and further improve the high-temperature performance of the asphalt. At the same time, the rubber and latex components in the rubber band enhance the overall performance of the asphalt under high and low temperature conditions through the viscoelastic effect of the polymer chain: the long-chain cross-linking of the rubber makes the asphalt show higher shear stability at high temperatures, while the latex component helps the rubber to be evenly dispersed in the asphalt matrix, enhancing its cohesion, thereby improving crack resistance and fatigue resistance.

[0031] 3. The trace mineral components in the filler also act as microscopic fillers in the matrix asphalt, enhancing the density of the composite material and helping to reduce the initiation of micro cracks, thereby further improving the durability and fatigue resistance of the asphalt. The vulcanization process causes the rubber chains to cross-link, forming a stable network structure, limiting the fluidity of the asphalt at high temperatures, significantly enhancing its ability to resist permanent deformation, especially in suppressing rutting.

[0032] In summary, the modifier made from waste rubber bands can not only improve the high-temperature stability, toughness and fatigue resistance of ordinary asphalt, but also achieve important benefits in waste resource utilization and environmental protection, providing a green and high-performance modification option for asphalt binder. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a dynamic shear rheology (DSR) test diagram in an embodiment of the present invention;

[0035] Figure 2 This is a test diagram of multiple stress creep recovery (MSCR) in an embodiment of the present invention;

[0036] Figure 3 This is a microscopic dispersion state diagram of the low-carbon high-stability modified asphalt in Example 5 of the present invention;

[0037] Figure 4 This is a microscopic dispersion state diagram of the rubber modified asphalt in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0039] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0040] In the embodiments of the present invention, the specific sources of various materials are as follows:

[0041] Reagents / Materials Commercial Origin 70# Base Asphalt Sinopec Jinling Petrochemical Company Stabilizer Henan Noah Biotechnology Co., Ltd. Accelerator Shanghai Aladdin Biochemical Technology Co., Ltd. Waste rubber band Changsha waste plastic processing plant self-collection Waste tires Guangxi Jiaoke Group Co., Ltd.

[0042] Example 1

[0043] A low-carbon and high-stability modified asphalt comprises a base asphalt, a low-carbon and high-stability asphalt modifier and a sulfur stabilizer, wherein the amount of the low-carbon and high-stability asphalt modifier is 2-10wt% of the base asphalt, the amount of the stabilizer is 0.2wt% of the base asphalt, and the amount of the accelerator is 1.5 times the amount of the stabilizer.

[0044] The low-carbon high-stability asphalt modifier is in a natural storage state, and is obtained by pre-treatment of waste rubber bands stored for 3 to 6 months, with a latex content of 63%. The treatment method for waste rubber bands is:

[0045] The waste rubber bands collected from the garbage recycling plant are placed in a pulsator cleaning machine to remove surface stains for 2 to 3 hours; the washed waste rubber bands are placed in an oven, the drying temperature is controlled at 80°C, and the drying time is 3 hours; the dried waste rubber bands are crushed and ground using a rubber mill (grinding shaft type), and then sieved to obtain a low-carbon asphalt modifier with a particle size of ≤40 mesh.

[0046] A method for preparing low-carbon and high-stability modified asphalt comprises the following steps:

[0047] S1. Prepare a low-carbon and high-stability asphalt modifier for standby use;

[0048] S2, heat 70# base asphalt at 135℃ for 30min to melt it, then add 2wt% of low-carbon high-stability asphalt modifier prepared by S1, control the temperature at 165℃, and stir it for 10min;

[0049] S3. After preliminary stirring, the mixed material is subjected to high-speed shearing for 50 min, the shear rate is controlled at 4500 r / min, and the temperature is controlled at 170°C;

[0050] S4, add 0.2wt% of stabilizer, control the temperature at 175℃, stir for 5min; then disperse and stir at a rate of 450rad / min, control the time of high-speed dispersion and stirring at 20min, and control the temperature at 175℃;

[0051] S5. Add accelerator in an amount 1.5 times that of stabilizer, and perform high-speed dispersion stirring at a rate of 500 rad / min. The time is controlled within 25 minutes and the temperature is controlled at 175 degrees Celsius to obtain low-carbon and high-temperature modified asphalt.

[0052] Example 2

[0053] The difference between this embodiment and embodiment 1 is that the dosage of the low-carbon high-stability modifier prepared in embodiment 1 in step S2 is 4%.

[0054] Example 3

[0055] The difference between this embodiment and embodiment 1 is that the dosage of the low-carbon high-stability modifier prepared in embodiment 1 in step S2 is 6%.

[0056] Example 4

[0057] The difference between this embodiment and embodiment 1 is that the dosage of the low-carbon high-stability modifier prepared in embodiment 1 in step S2 is 8%.

[0058] Example 5

[0059] The difference between this embodiment and embodiment 2 is that the dosage of the low-carbon high-stability modifier prepared in embodiment 1 in step S2 is 10%.

[0060] Comparative Example 1

[0061] According to the method in Example 1, in step S2, the low-carbon high-stability modifier prepared in Example 1 is replaced by waste tire rubber in an amount of 2%.

[0062] Comparative Example 2

[0063] According to the method in Example 1, in step S2, the low-carbon high-stability modifier prepared in Example 1 is replaced by waste tire rubber in an amount of 6%.

[0064] Comparative Example 3

[0065] According to the method in Example 1, in step S2, the low-carbon high-stability modifier prepared in Example 1 is replaced by waste tire rubber in an amount of 6%.

[0066] Comparative Example 4

[0067] According to the method in Example 1, in step S2, the low-carbon high-stability modifier prepared in Example 1 is replaced by waste tire rubber in an amount of 8%.

[0068] Comparative Example 5

[0069] According to the method in Example 1, in step S2, the low-carbon high-stability modifier prepared in Example 1 is replaced by waste tire rubber in an amount of 10%.

[0070] Comparative Example 6

[0071] Unmodified 70# base asphalt was used as a blank control group, recorded as Comparative Example 6.

[0072] In order to verify the feasibility and effectiveness of the present invention, the following performance tests were performed on the modified asphalts prepared in the above embodiments and comparative examples:

[0073] 1. The modified asphalt or asphalt prepared in the above embodiments and comparative examples was subjected to asphalt penetration test, ductility test, softening point test (ring and ball method), rotational viscosity test, 135°C rotational viscosity test and segregation test according to the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering". The test results are shown in Table 1.

[0074] 2. The modified asphalt or asphalt prepared in the above examples and comparative examples was subjected to the dynamic shear rheology (DSR) test and the multiple stress creep recovery (MSCR) test of asphalt according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering". The test results are as follows: Figure 1 , Figure 2 shown.

[0075] 3. The modified asphalt prepared in the above-mentioned Experimental Example 5 and Comparative Example 5 was prepared into test pieces according to the Standard Guide for Reflected Light Microphotography ASTM E883, and the microscopic dispersion state of the modified asphalt prepared in Example 5 of the present invention and the rubber modified asphalt in Comparative Example 5 was observed under a fluorescence microscope. Figure 3 and 4 shown.

[0076] Table 1 Basic performance test results of modified asphalt or asphalt in various embodiments and comparative examples

[0077]

[0078]

[0079] From the data in Table 1, it can be seen that after the base asphalt is modified by the low-carbon and high-stability asphalt modifier prepared by the present invention using waste rubber bands as raw materials, when the dosage is 2%, 4%, 6%, 8% and 10%, the penetration of the modified asphalt is reduced by 22.8%, 24.1%, 25.1%, 26.8% and 28.4% respectively compared with the unmodified asphalt; the softening point is increased by 13.5%, 15.7%, 19.8%, 22.8% and 28.2°C respectively. Compared with the tire rubber modified asphalt with the same dosage, the low-carbon and high-stability modified asphalt prepared by the present invention has better improvement effects on penetration and softening point than the tire rubber modified asphalt when the dosage is less than 8%. This may be because the latex (natural rubber) content in the modifier prepared by the present invention is higher than that of tire rubber, and the degree of vulcanization is low, so that the low-carbon and high-stability asphalt modifier has better dispersibility in the base asphalt. At lower dosage (<8%), the modifier has a more significant effect on improving the high temperature stability of asphalt.

[0080] In addition, it can be seen from the data that the low-carbon and high-stability asphalt modifier provided by the present invention has better compatibility with the base asphalt than tire rubber. This is manifested in that the segregation temperature difference of the modified asphalt due to the thermodynamic incompatibility between the modifier and the base asphalt is smaller than that of the tire rubber modified asphalt, which meets the requirement of the "Technical Specifications for Highway Asphalt Pavement Construction" that the softening point difference is less than 3°C.

[0081] Further analysis shows that the ductility of the modified asphalt prepared from waste rubber bands at 10°C is better than that of the modified asphalt with the same dosage of tire rubber, which shows that it performs better in low-temperature crack resistance. This is attributed to the high content of natural rubber in the low-carbon and high-stability asphalt modifier, whose molecular chain structure has better flexibility and elasticity, thus making the modified asphalt have better ductility and resilience at low temperatures.

[0082] In terms of construction performance, the low-carbon and high-stability modified asphalt of the present invention has a rotational viscosity of less than 3 Pa·s at 135°C when the dosage is 8% or less. This shows that compared with tire rubber modified asphalt, the low-carbon and high-stability modified asphalt prepared by the present invention can be constructed at a lower construction temperature, which helps to reduce the energy consumption of asphalt when it is heated to the construction temperature, thereby reducing the loss of petroleum resources and carbon emissions.

[0083] from Figure 1It can be seen that with the increase of the asphalt modifier dosage, the rutting factor is significantly improved. When the modifier dosage is 2%, 4%, 6%, 8%, and 10%, the rutting factor is increased by 0.50, 0.72, 2.04, 2.81, and 2.98 times compared with ordinary petroleum asphalt, respectively. This shows that asphalt modifiers can significantly enhance the deformation resistance of ordinary petroleum asphalt, thereby improving its high temperature performance. The low-carbon and high-stability modified asphalt prepared in each embodiment of the present invention, when the dosage is less than 8%, its rutting factor is higher than that of the tire rubber modified asphalt with the corresponding dosage, and this conclusion is consistent with the data trend of the needle penetration and softening point in Table 1.

[0084] from Figure 2 It can be seen from the analysis that as the dosage of the asphalt modifier of the present invention increases, the irrecoverable creep compliance of the asphalt also increases. When the dosage is 2%, 4%, 6%, 8%, and 10%, the recovery rate of ordinary petroleum asphalt is reduced by 62.12%, 87.88%, 90.17%, 91.89%, and 93.09%, respectively. This shows that the addition of asphalt modifier significantly improves the elastic recovery performance of ordinary petroleum asphalt, which is consistent with the trend of the 10°C ductility data in Table 1. This is attributed to the fact that the high content of natural rubber in the low-carbon and high-stable asphalt modifier significantly enhances the ductility and elastic recovery ability of the base asphalt.

[0085] Now, the above conclusions are studied in depth. The raw materials of the low-carbon and high-stable asphalt modifier of the present invention are waste rubber bands, which are aged by environmental conditions such as thermal oxidation and ultraviolet rays during the waste process. Heat and thermal oxidation aging can cause chain breaking in natural rubber, but at the same time, oxide free radicals are generated to continue vulcanization and bonding. In this process, bond breaking and bonding are in a competitive relationship, but bonding has an advantage. As the aging time increases, the density of EAC (elastic active chain) increases, the spatial distribution of vulcanization cross-linking becomes heterogeneous, and the pores of natural rubber increase. The elastic active chain has a high degree of freedom and can be stretched or bent under the action of external force, and then return to its original shape. This makes the elastic recovery of natural rubber after thermal oxidation aging improve, and the rigidity is reduced, thereby improving the problem of natural rubber becoming brittle at low temperatures, but the thermal stability is reduced due to the increase in EAC density. The low-carbon and high-stable asphalt modifier of the present invention is mixed into petroleum asphalt, and the porous natural rubber can effectively absorb the light components in petroleum asphalt, relatively increasing the asphaltene content, thereby improving the high-temperature stability of asphalt, which is reflected in the increase in softening point and the decrease in needle penetration. At the same time, the increase in EAC density further improves the low-temperature performance of asphalt, thereby having a synergistic effect of high and low temperature stability.

[0086] At the micro level, Figure 3 and Figure 4It shows that compared with tire rubber, the droplet size of low-carbon and high-stability asphalt modifier in the base asphalt is smaller, the distribution is more uniform, and the dispersion effect is better. This further explains the compatibility of the modifier with the base asphalt and its effect on the rotational viscosity. The smaller droplet size means that the polymer has a lower degree of agglomeration and is more evenly distributed in the base asphalt, which helps to improve the construction mixing efficiency.

[0087] In summary, compared with tire rubber, waste rubber bands have better performance in asphalt modification, mainly reflected in:

[0088] (1) Pore adsorption effect: Tire rubber usually does not have a porous structure, and the low-carbon and high-stability asphalt modifier of the present invention has a low efficiency in adsorbing light components in asphalt; the pore structure of waste rubber bands relatively increases the asphaltene content of the modified asphalt, thereby improving the high-temperature performance.

[0089] (2) Dispersion uniformity: Tire rubber is difficult to effectively shear and disperse due to its large molecular weight and high degree of vulcanization. It is prone to aggregation, resulting in uneven distribution in the asphalt matrix. Scrap rubber bands have a small molecular weight and a low degree of vulcanization, so the modification effect is more significant.

[0090] (3) Synergistic effect of elastic active chains: After vulcanization, the cross-linking structure of tire rubber has been fixed, the number of EAC is small, and the elasticity is limited, which is reflected in strength and durability; while the EAC density in waste rubber bands is higher, and it shows better elastic recovery and deformation ability in asphalt.

[0091] The scheme of the present invention not only promotes the recycling of waste rubber, but also provides new market opportunities for waste rubber products that are not recycled due to low economic value. By applying waste rubber bands to asphalt modification, not only the comprehensive properties of ordinary petroleum asphalt are greatly improved, especially its low temperature and creep resistance, but also the service life of asphalt pavement is effectively improved. This scheme provides a feasible path for the resource utilization of waste rubber and environmental protection, and helps to promote the development of green transportation infrastructure.

[0092] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A low-carbon and high-stability modified asphalt, characterized in that: It includes base asphalt, a low-carbon and high-stability asphalt modifier, a stabilizer and a promoter, wherein the dosage of the low-carbon and high-stability asphalt modifier is 2-10wt% of the base asphalt, the dosage of the stabilizer is 0.2-0.3wt% of the base asphalt, and the dosage of the promoter is 0.75-1.75 times that of the stabilizer.

2. A low-carbon and high-stability modified asphalt according to claim 1, characterized in that: The low-carbon and high-stability asphalt modifier is obtained by pre-treating waste rubber bands that have been stored for 3 to 6 months in a natural outdoor waste accumulation state, and has a latex content of 60 to 70%.

3. A low-carbon and high-stability modified asphalt according to claim 2, characterized in that: The method for processing the waste rubber bands is as follows: the waste rubber bands are placed in a pulsator cleaning machine for cleaning, the dried waste rubber bands are ground by a rubber grinder, and after grinding, they are sieved to obtain a low-carbon and high-stability asphalt modifier with a particle size of ≤40 mesh.

4. A low-carbon and high-stability modified asphalt according to claim 3, characterized in that: The cleaning time is 2~3h, and the drying conditions are at 75℃~90℃ for 2h~4h.

5. The low-carbon and high-stability modified asphalt according to claim 1, characterized in that: The stabilizer is sulfur.

6. The low-carbon and high-stability modified asphalt according to claim 1, characterized in that: The accelerator is N-cyclohexyl-2-benzothiazole sulfenamide.

7. The method for preparing a low-carbon and high-stability modified asphalt according to any one of claims 1 to 6, characterized in that: The steps include: S1. Prepare a low-carbon and high-stability asphalt modifier for standby use; S2, heat the base asphalt at 130-140℃ for 30-35min to melt it, then add 2-10wt% of the low-carbon and high-stability asphalt modifier prepared by S1, control the temperature at 160-165℃, and stir it preliminarily; S3. After preliminary stirring, the mixed material is subjected to high-speed shearing for 40-50 minutes, and the temperature is controlled at 170-175°C; S4, add 0.2~0.3wt% of stabilizer, control the temperature at 170~180℃, stir and mix evenly for a second time, and then disperse and stir at a rate of 400~500rad / min; S5. Add accelerator at a dosage of 0.75~1.75 times of stabilizer, continue high-speed dispersion stirring at a rate of 400~500rad / min, control the time at 20~25min, and control the temperature at 175±3℃ to obtain low-carbon and high-temperature modified asphalt.

8. The method for preparing a low-carbon and high-stability modified asphalt according to claim 7, characterized in that: In step S2, the initial stirring time is 10 to 15 minutes.

9. The method for preparing a low-carbon and high-stability modified asphalt according to claim 7, characterized in that: In step S3, the high-speed shear rate is 4500-5000 r / min.

10. The method for preparing a low-carbon and high-stability modified asphalt according to claim 7, characterized in that: In step S4, the secondary stirring time is 5-10 min, the high-speed dispersion stirring time is controlled at 15-25 min, and the temperature is controlled at 170-180°C.

Citation Information

Patent Citations

  • Waste polymer glove modified asphalt and preparation method thereof

    CN117624923A